Kinerja Agribisnis Kelapa Sawit Rakyat di Provinsi Sumatera Utara - Suardi, Tennisya Febriyanti; Zahraturrahmi, Zahraturrahmi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The development of palm oil plantation area in North Sumatra was in fact less supported by the resulting productivity has not been matched by corresponding productivity levels. Smallholder palm oil plantations in North Sumatra Province have productivity that tends to be low so that appropriate agribusiness management is needed for the development of palm oil commodities to minimize the production and productivity gap that occurs. This study aims to analyze the performance of smallholder palm oil agribusiness systems based on five agribusiness subsystems. A quantitative research method was employed. The determination of smallholder palm oil farmer respondents was based on stratified random sampling techniques from 33 cities/districts in North Sumatra. A total of 124 smallholder palm oil farmer respondents were sampled. The research data were collected through primary and secondary sources. The data analysis design used was descriptive analysis using the Method of Successive Interval (MSI). The results showed that the performance of the smallholder palm oil agribusiness system was in the good category. The result handling subsystem is perceived by farmers as more important and more prioritized than the input subsystem, production subsystem, marketing subsystem, and supporting subsystem. The yield handling subsystem will affect the quality of fresh fruit bunches and the yield of palm oil produced. It is necessary to strengthen the role of farmer-level institutions in palm oil processing and marketing in order to improve the bargaining position of farmers through efforts to improve the ability of farmers and increase good cooperation.